Evaluation of two molecular techniques for rapid detection of the main dermatophytic agents of tinea capitis. (19th November 2015) - Deng, S.; Zhou, Z.; de Hoog, G.S.; Wang, X.; Abliz, P.; Sun, J.; Najafzadeh, M.J.; Pan, W.; Lei, W.; Zhu, S.; Hasimu, H.; Zhang, P.; et al.
Abstract : What's already known about this topic? Children in western regions of China are at high risk of infection, with the most widespread aetiological agent beings Trichophyton violaceum and Microsporum canis . Due to the high degree of phenotypic pleomorphism and the close phylogenetic relationship among dermatophytes, identification problems are inherent. Rolling circle amplification (RCA) and multiplex ligation‐dependent probe amplification (MLPA) have not yet been applied in the detection of dermatophytic agents of tinea capitis. What does this study add? Our data show that both RCA and MLPA are highly sensitive and accurate tools for the distinction of T. violaceum and M. canis from closely related molecular siblings. RCA and MLPA are advantageous in their reliability and ease of operation compared with standard polymerase chain reaction and conventional methods. Linked Comment: Hay, Br J Dermatol 2015; 173: 1368–69 . Summary: Background: Tinea capitis is very common in Western China, with the most widespread aetiological agent being Trichophyton violaceum, while Microsporum canis is prevalent in the remainder of China. Conventional diagnostics and internal transcribed spacer (ITS) sequencing analyses have proven relatively limited due to the close phylogenetic relationship of anthropophilic dermatophytes. Therefore, alternative molecular tools with sufficient specificity, reproducibility and sensitivity are necessary. Objectives: To evaluate two molecular techniques [multiplex ligation‐dependent probe amplification (MLPA) and rolling circle amplification (RCA)] for rapid detection of the aetiological agents of tinea capitis, T. violaceum and M. canis . Methods: Probes of RCA and MLPA were designed with target sequences in the rDNA ITS gene region. Strains tested consist of 31 T. violaceum, 22 M. canis and 24 reference strains of species that are taxonomically close to the target species. Results: The specificity and reproducibility of RCA and MLPA in detection of T. violaceum and M. canis were both 100% in both species. Sensitivity testing showed that RCA was positive at concentrations down to 1·68 × 10 6 copies of DNA in the TvioRCA probe, and 2·7 × 10 8 copies of DNA in McRCA. MLPA yielded positive results at concentrations of DNA down to 1·68 × 10 1 copies in the TvioMLPA probe and 2·7 × 10 2 in McMLPA. Conclusions: The two techniques were sufficiently specific and sensitive for discriminating the target DNA of T. violaceum and M. canis from that of closely related dermatophytes. RCA and MLPA are advantageous in their reliability and ease of operation compared with standard polymerase chain reaction and conventional methods.